Peran Hukum Bisnis dalam Memberikan Perlindungan Hukum bagi Pelaku Usaha di Indonesia - Mahardika Dwi Candra; Rifky Ardhana Tirta; Dinda Adwhaa Syahbila; Olivia Amanda; Athita Alhayu; Helfira Citra, S.H., M.H (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2025)
The rapid development of the business world driven by globalization and technological advancement has significantly transformed business activities, including the emergence of digital transactions and electronic contracts. These changes demand legal certainty to ensure fairness, order, and protection for all parties involved. This paper aims to analyze the role of business law in providing legal protection for business actors, regulating business agreements, resolving business disputes, and responding to challenges in digital business practices in Indonesia. The method used in this study is a normative juridical approach through the analysis of laws and regulations, legal doctrines, and relevant literature related to business law. The results show that business law plays a crucial role in ensuring legal certainty through contract regulation, promoting good faith and trust between parties, and providing dispute resolution mechanisms through litigation and non-litigation channels. Furthermore, business law has adapted to digital business developments by recognizing the legal validity of electronic contracts and emphasizing consumer protection and data security. Therefore, effective implementation of business law is essential to create a healthy, secure, and sustainable business environment in Indonesia.